Understanding the phases and objectives of the career development process in the context of successful career management - Ilić Đurđijana (Trendovi u Poslovanju)
The basis of a quality organization consists of reliable employees who are satisfied with their work, ready to learn and progress, and thus continuously bring profit and progress to themselves and the organization. The foundation of a quality organization consists of a quality corporate mission, a reasonable vision of the organization, clearly set goals and a high level of creativity and innovation of employees, aimed at fulfilling the mission, vision and goals. Employees who are dissatisfied will not do the job properly, which is why the organization suffers direct material damage. Dissatisfied employees will want to leave the job, which speaks in favor of the fact that the resources previously invested in that employee were not used in accordance with the mission of the organization. In order for the organization to operate successfully and make profit, it is necessary to constantly control and maintain the career progress and satisfaction of employees, because its success is based on satisfied and advanced human resources. Career implies advancement, progress, occupation with the profession and stability, which is often considered as its basic precondition. That the concept of career development is extremely complex is shown by the fact that it has produced a large number of organizational phenomena that are intensively studied. Knowing, understanding and following the different stages of the career development process, as well as the numerous and diverse goals of the career development process can significantly contribute to the successful operation of organizations.